[Re 6 Q 8 (SO 3 ) 6 ] 10– (Q = S or Se): Facile Synthesis and Properties of the Most Highly Charged Octahedral Cluster Complexes and High Magnetic Relaxivity of Their Colloids with Gd 3+ Ions - Brylev, Konstantin A.; Akhmadeev, Bulat S.; Elistratova, Julia G.; Nizameev, Irek R.; Gubaidullin, Aidar T.; Kholin, Kirill V.; Kashnik, Ilya V.; Kitamura, Noboru; Kim, Sung-Jin; Mironov, Yuri V.; Mustafina, Asiya R. (Inorganic chemistry, 2019)
New octahedral rhenium cluster complexes [Re Q (SO ) ] (Q = S or Se) were synthesized starting from [Re Q (H O) (OH) ]·12H O. The complexes were crystallized as sodium salts and characterized by X-ray single-crystal diffraction and elemental analyses, IR, UV/vis and luminescence spectroscopies. Magnetic relaxation data demonstrate the complex formation of the cluster units with gadolinium ions. The analysis of the magnetic relaxation rates measured at various Gd:cluster ratios and different concentrations revealed the conversion of the aggregates (Gd [Re Se (SO ) ] ) into a nanoparticulate form even at = 1 and ≥ 1. Thus, the self-assembly of the cluster units into the nanoparticles is greatly facilitated by counterion binding with sodium cations. The concentration conditions were optimized for the formation and hydrophilization of Na Gd [Re Q (SO ) ]-based colloids with the magnetic relaxivity values of = 21.0(24.1) and = 25.9(29.8) mM s for the Re S and Re Se derivatives, respectively.